Muslim Leadership in the United States: A Case Study of Zohran Mamdani as the First Muslim Mayor of New York - Nurcahya, Yan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the emergence of Muslim leadership in the United States through the case of Zohran Mamdani, recognized as the first Muslim mayor in New York City. His political journey represents a significant shift in the visibility and participation of Muslim Americans within the multicultural and pluralistic landscape of U.S. politics. The research aims to analyze how Mamdani’s leadership style, socio-political engagement, and community-oriented policies reflect both Islamic ethical values and the democratic principles of American governance. Using a qualitative approach and sociopolitical analysis, this paper explores the intersections of faith, identity, and civic participation in Mamdani’s political career. The findings highlight his advocacy for social justice, racial equality, and economic reform as manifestations of an inclusive and progressive form of Muslim leadership. Furthermore, Mamdani’s success challenges stereotypes about Islam in Western political contexts and demonstrates the evolving role of Muslim citizens in shaping public discourse and policy. In conclusion, Zohran Mamdani’s leadership embodies a new paradigm of Muslim representation in American politics — one that balances faith-based values with civic responsibility, contributing to a more equitable and multicultural democratic society.